2015
DOI: 10.1002/pat.3581
|View full text |Cite
|
Sign up to set email alerts
|

Melt rheology and thermomechanical behavior of poly(methyl methacrylate)/reduced graphene oxide nanocomposites

Abstract: Thermomechanical and rheological behavior of poly(methyl methacrylate) (PMMA)/reduced graphene oxide (RGO) nanocomposites prepared via in situ polymerization using sheet casting method was investigated. Scanning electron microscope and transmission electron microscope were used to study the microstructure of nanocomposites in terms of dispersion of RGO and polymer-RGO interaction. The thermomechanical properties were investigated using dynamic mechanical analyzer, and it was found that the incorporation of RGO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Previous studies reported large increases in T g with small additions of graphene to a variety of polymers [36,38,39] and speculate that this large shift is due to chain interaction on the surface of graphene with attached functional groups. [36]…”
Section: Mechanical Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies reported large increases in T g with small additions of graphene to a variety of polymers [36,38,39] and speculate that this large shift is due to chain interaction on the surface of graphene with attached functional groups. [36]…”
Section: Mechanical Propertiesmentioning
confidence: 88%
“…Similar increases have been reported with other graphene-polymer composites and other polymer nanocomposites. [36,37] Furthermore, T g increase from 152 °C to 166 °C for PEEK and 5Gn-PEEK, respectively, as measured by the loss modulus (G") peak maximum.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…The effect of reduced graphene oxide (RGO) on melt rheological properties of poly(methyl methacrylate) (PMMA) were analyzed. 12 They have found that moduli and viscosity of PMMA/RGO nanocomposites increased with increase in RGO loading, and a decrease in viscosity was observed with increasing frequency indicating a shear thinning behaviour. 12 Recently, rheological properties of three different nanocomposites, consisting of graphene oxide (GO), RGO, and polyhedral oligomeric silsesquioxane graed reduced graphene oxide (RGO-POSS) as nanollers with poly dimethyl siloxane (PDMS) matrices, were investigated by large amplitude oscillatory shear (LAOS).…”
Section: Introductionmentioning
confidence: 98%
“…12 They have found that moduli and viscosity of PMMA/RGO nanocomposites increased with increase in RGO loading, and a decrease in viscosity was observed with increasing frequency indicating a shear thinning behaviour. 12 Recently, rheological properties of three different nanocomposites, consisting of graphene oxide (GO), RGO, and polyhedral oligomeric silsesquioxane graed reduced graphene oxide (RGO-POSS) as nanollers with poly dimethyl siloxane (PDMS) matrices, were investigated by large amplitude oscillatory shear (LAOS). 13 They have noticed that different surface functionalization of nanoparticles resulted in different rheological behaviour due to the formation of different network-like structures.…”
Section: Introductionmentioning
confidence: 98%
“…Since then, more attention has been paid to rheological properties of graphene/polymer nanocomposites focusing on the percolation threshold as one of the most important factors affecting the material properties or as a characterization parameter of the dispersion quality. Such a percolated system was studied by using polycarbonate/graphene composites , poly(propylene)/graphene nanocomposites , poly(methyl methacrylate)/graphene composites , and poly(methyl methacrylate)/reduced graphene oxide nanocomposites .…”
Section: Introductionmentioning
confidence: 99%